Go red for women 2011 : awareness campaign to educate Singaporean women on cardiovascular disease being their number one killer. - Khor, Ying Heng. (2011)
This paper presents the collaboration between a group of four final-year students from the Wee Kim Wee School of Communication and Information, Nanyang Technological University, and the Singapore Heart Foundation. The communications campaign set out to increase the awareness of the issue of cardiovascular disease, the number one killer of women in Singapore, among females aged 25 to 45. This paper includes research that shaped the direction of communication messaging, detailed strategies and mechanics, and a detailed evaluation of the team's efforts.